The ox fall down: path-breaking and technology treadmills in Indian cotton agriculture - Stone, Glenn Davis; Flachs, Andrew (The journal of peasant studies, 2017)
Although India’s cotton sector has been penetrated by various input- and capital-intensive methods, penetration by herbicide has been largely stymied. In Telangana State, the main obstacle has been the practice of ‘double-lining’, in which cotton plants are spaced widely to allow weeding by ox-plow. Path dependency theory primarily explains the persistence of sub-optimal practices, but double-lining is an example of an advantageous path for cash-poor farmers. However, it is being actively undermined by parties intent on expanding herbicide markets and opening a niche for next-generation genetically modified cotton. We use the case to explicate the role of treadmills in technology ‘lock-in’. We also examine how an adaptive locked-in path may be broken by external interests, drawing on recent analyses of ‘didactic’ learning by farmers.